Mortality After High-Energy Pelvic Fractures in Patients of Age 65 Years or Older. Issue 3 (March 2018) - Keil, Dayley S.; Gross, Steven; Seymour, Rachel B.; Sims, Stephen; Karunakar, Madhav A.
Abstract : Objectives: To document in-hospital and 1-year mortality rates after high-energy pelvic fracture in patients 65 years of age or older as compared to a younger cohort. Design: Retrospective review. Setting: Urban Level 1 academic trauma center. Patients: Seventy consecutive patients 65 years of age and older treated for pelvic fracture resulting from high-energy mechanism from 2008 to 2011. A total of 140 patients 18–64 years of age were matched to the study population based on mechanism of injury and OTA Code 61 subtype for comparison. Intervention: Review of demographics, injury characteristics, hospital management, and mortality. Main Outcome Measurements: Mortality. Results: The overall inpatient mortality rate was 10%. The older cohort exhibited an inpatient mortality rate 3 times higher than the younger cohort (18.6% vs. 5.7%, P = 0.003). There was no difference in mortality 1 year post discharge (5.3% vs. 3.8%, P = 0.699). No significant differences in initial Glasgow Coma Scale or Injury Severity Score were identified (GCS 12.9 vs. 12.4, P = 0.363; ISS 24.7 vs. 23.4, P = 0.479). Multivariate analysis identified the Charlson Comorbidity Index (CCI) ( P = 0.012) and Abbreviated Injury Scale (AIS)-chest ( P = 0.005) as independent predictors of in-hospital mortality, and CCI (0.005) and AIS-abdomen (0.012) for 1-year mortality. Conclusions: After controlling for mechanism of injury and pelvic fracture classification, we found that adults ≥65 and those with multiple comorbidities were more likely to die in the hospital than younger adults. However, mortality within 1-year postdischarge was low and did not differ between groups. This is in sharp contrast to the high rates of postdischarge mortality observed in elderly patients with a hip fracture. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.